Atividade respiratória para a separação de lotes de sementes de soja, feijão e milho - Martins, Andréa Bicca Noguez (2013)
The seed quality is usually assessed by patterns of germination and vigor, however, on lots with a high degree of heterogeneity, these tests may show low sensitivity. So, it is necessary to obtain reliable results in short time, ensuring the speediness in decision in relation to the seed quality. Thus, this work was developed aiming to separate seed lots of soybean, bean and corn, according to its vigour through the respiratory activity. For this, three seed lots of crops, were submitted patterns of seed quality, such as germination, first count germination, germination speed index, electrical conductivity, emergency seedlings in the greenhouse, speed emergency, length and dry mass of shoots and roots of seedlings from the germination tests and emergency of seedlings and respiratory activity. According to the results of patterns of physiological quality of soybean seeds was evidenced lot two as the most vigorous and seeds of beans and corn, lots three corroborating with the results regarding the respiratory activity of the seeds. Therefore, we conclude that the respiratory activity allows to separate lots of seeds of of soybean, bean and corn according to its vigour.